1999
DOI: 10.1037/0893-164x.13.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of positive and negative affect to adolescent substance use: Test of a bidimensional model in a longitudinal study.

Abstract: Contributions of bidimensional affect measures to adolescent substance (tobacco, alcohol, and marijuana) use were measured. Participants (baseline N = 1,702) were surveyed at age 12.4 years and followed longitudinally through age 15.4 years. Multiple regression indicated negative affect related to higher levels of substance use and positive affect related to lower levels of substance use. Buffer interactions indicated that the relationship of negative affect to substance use was reduced among persons with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 48 publications
11
141
0
2
Order By: Relevance
“…One possibility is that low NMR may promote substance abuse as a means of coping with affective distress (Catanzaro & Laurent, 2004). Reduction of negative affect is a major reason cited for using alcohol and drugs (Johnston & O'Malley, 1986;Newcomb et al, 1988) and high negative affect is related to consuming greater amounts of drugs and alcohol (Colder & Chassin, 1993;Krueger et al, 1996;Wills et al, 1999). Much previous research has also found significantly higher NMR Expectancies 11 levels of stress (e.g., Blume, Marlatt & Schmaling, 2000;Gorman, 1988;Horowitz & Davies, 1994;Shoal & Giancola, 2001), anxiety disorders (e.g., Compton et al, 2000;Schuckit et al, 1997;Weiss & Rosenberg, 1985) and mood disorders (Raimo & Schuckit, 1998;Swendsen & Merikangas, 2000;Tomasson & Vaglum, 1995) among those with substance problems compared to non-addict control samples.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that low NMR may promote substance abuse as a means of coping with affective distress (Catanzaro & Laurent, 2004). Reduction of negative affect is a major reason cited for using alcohol and drugs (Johnston & O'Malley, 1986;Newcomb et al, 1988) and high negative affect is related to consuming greater amounts of drugs and alcohol (Colder & Chassin, 1993;Krueger et al, 1996;Wills et al, 1999). Much previous research has also found significantly higher NMR Expectancies 11 levels of stress (e.g., Blume, Marlatt & Schmaling, 2000;Gorman, 1988;Horowitz & Davies, 1994;Shoal & Giancola, 2001), anxiety disorders (e.g., Compton et al, 2000;Schuckit et al, 1997;Weiss & Rosenberg, 1985) and mood disorders (Raimo & Schuckit, 1998;Swendsen & Merikangas, 2000;Tomasson & Vaglum, 1995) among those with substance problems compared to non-addict control samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research examining individuals who have a parent with a substance-use disorder has found that they exhibit higher levels of negative affect in comparison with those that do not have a parent with a substance-use disorder (Chassin and Ritter, 2001;Clark et al, 1999;Shoal and Giancola, 2001). Negative affect also has been linked to substance use during adolescence (Desrichard and Denarie, 2005;Hussong and Hicks, 2003;Shoal and Giancola, 2001;Wills et al, 1999).…”
Section: Negative Affect and Substance Usementioning
confidence: 99%
“…Among adolescents with SUD, elevated rates of negative affect disorders and related symptoms have been reported, with higher rates among females than among male SUD adolescents (40). Also, depressed mood has been shown to positively predict drug use (19,41,42) as well as drug use problems (43,44) among teenagers. These findings are consistent with both the self-medication hypothesis (45,46), which advances that individuals use substances to alleviate symptoms of dysphoria and or anxiety, and with developmental theories suggesting that negative affect provides another important etiologic pathway leading to the development of SUDs (32,14).…”
Section: Psychological Disturbancementioning
confidence: 99%